Dynamics of the ion energy distribution and plasma parameters in flows of the non-self-sustained arc discharge in molybdenum vapors - Borisenko, A.G. (Problems of Atomic Science and Technology, 2023)
In these experiments, the energy distribution functions of ions and plasma parameters in the generated flows of a non-self-sustained arc discharge in pure molybdenum vapors and in a mixture of molybdenum vapors with gas were investigated. It is proved that there are practically no ions with energy over 100 eV in the flows, and that the maximum of the ion distribution function shifts to lower values of the ion energy when the vacuum arc discharge current increases. The values of the plasma potential in the flows, the density and temperature of the plasma electrons at different discharge currents were determined. It is shown that the working medium of the discharge in pure molybdenum vapors is formed during the diffuse evaporation of the working material, which ensures the absence of droplets of the working material in the generated flows. Growth rates of deposited molybdenum films at different operating modes of the discharge were determined. It has been proven that the plasma flow created by a discharge of this type in molybdenum vapors has a compensated volume charge and can be used to apply metal films and coatings to substrates made of various materials, including dielectric ones. У цих експериментах були досліджені функції розподілу іонів за енергією в плазмових потоках несамостійного дугового розряду в чистих парах молібдену та параметри плазми в генерованих потоках. Доведено, що максимум функції розподілу іонів за енергією зміщується до менших значень енергії іонів при збільшенні струму вакуумного дугового розряду. Визначені значення потенціалу плазми в потоках, густина та температура електронів плазми при різних струмах розряду. Показано, що робоче середовище розряду в чистих парах молібдену формується при дифузному випаровуванні робочого матеріалу, що забезпечує відсутність у створюваних потоках крапель робочого матеріалу. Визначені швидкості росту осаджуваних плівок молібдену в різних робочих режимах розряду. Доведено, що створюваний розрядом даного типу в парах молібдену плазмовий потік має компенсований об’ємний заряд і може бути використаним для нанесення металевих плівок і покриттів на підкладинки з різних матеріалів, у тому числі і діелектричних.